To solve the system of equations by substitution, we can substitute the value of x from the first equation into the second equation.
Given that x = -4y, we can substitute -4y for x in the second equation:
-4y + 5y = 2
Simplifying the equation:
y = 2
Now we can substitute this value of y back into the first equation to solve for x:
x = -4(2)
Simplifying:
x = -8
Therefore, the solution to the system of equations is (-8, 2).
Solve the system of equations by substitution.
x = –4y
x + 5y = 2
(1 point)
Responses
(–8, 2)
(–8, 2)
(8, –2)
(8, –2)
(two-ninths, –eight-ninths)
( Image with alt text: two-ninths , – Image with alt text: eight-ninths )
(–12, 3)
1 answer